Molecularly Imprinted Polymers (MIPs): Synthesis, Applications and Recent Advances in Water Remediation - Kapase, Shambhuraj A. (2025)
Molecularly imprinted polymers (MIPs) are an innovative class of synthetic materials designed for the selective recognition and binding of specific target molecules. With their unique ability to mimic biological recognition mechanisms, MIPs have gained significant attention across diverse fields, particularly for water purification, pollutant detection, and drug delivery applications. This review explores various synthesis techniques for MIPs, including sol–gel, electropolymerization, free radical, bulk, suspension, emulsion, precipitation, and advanced controlled polymerization methods such as atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain transfer (RAFT). The integration of MIPs with nanomaterials, magnetic particles, and stimuli-responsive systems has expanded their functionality, leading to improved sensitivity, stability, and reusability. Recent developments highlight the growing use of MIP-based sensors for real-time environmental monitoring, food safety analysis, and biomedical applications. Furthermore, advancements in photocatalytic degradation utilizing MIP composites offer promising solutions for efficient removal of pollutants from water. As interdisciplinary studies continue to evolve, MIPs are expected to play a crucial role in the development of next-generation technologies for environmental protection, healthcare, and industrial applications. Despite their extensive benefits, challenges remain in enhancing synthesis efficiency, stability, and selectivity, necessitating further research. The aim of this review is to provide latest collective information with comparative analysis of the synthesis methods and main applications of MIPs with emphasis on water remediation.